2017
DOI: 10.3390/molecules22122241
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Characterization of the Anthocyanidin Reductase Pathway Involved in the Biosynthesis of Flavan-3-ols in Elite Shuchazao Tea (Camellia sinensis) Cultivar in the Field

Abstract: Anthocyanidin reductase (ANR) is a key enzyme in the ANR biosynthetic pathway of flavan-3-ols and proanthocyanidins (PAs) in plants. Herein, we report characterization of the ANR pathway of flavan-3-ols in Shuchazao tea (Camellia sinesis), which is an elite and widely grown cultivar in China and is rich in flavan-3-ols providing with high nutritional value to human health. In our study, metabolic profiling was preformed to identify two conjugates and four aglycones of flavan-3-ols: (−)-epigallocatechin-gallate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Green tea (Zhao et al, 2017 ; Wang P. et al, 2020 ), two muscadine grape cultivar berries (including seeds and skin) (Yuzuak et al, 2018 ), and dark chocolate and cacao (Takahashi et al, 1999 ; Schewe et al, 2001 ) are rich in flavan-3-ol gallates and dimeric PAs. To understand whether these plant products could inhibit the M pro activity of SARS-Cov-2, we extracted flavan-3-ol gallates and dimeric PAs from the five types of materials and then completed in vitro assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Green tea (Zhao et al, 2017 ; Wang P. et al, 2020 ), two muscadine grape cultivar berries (including seeds and skin) (Yuzuak et al, 2018 ), and dark chocolate and cacao (Takahashi et al, 1999 ; Schewe et al, 2001 ) are rich in flavan-3-ol gallates and dimeric PAs. To understand whether these plant products could inhibit the M pro activity of SARS-Cov-2, we extracted flavan-3-ol gallates and dimeric PAs from the five types of materials and then completed in vitro assays.…”
Section: Resultsmentioning
confidence: 99%
“…At 10 μg/ml, the green tea extract tea completely inhibited the M pro activity ( Figure 7A ). In recent, we reported that green tea extracts contained a high content of EGCG, a relatively high content of ECG, and appropriate contents of dimeric procyanidin B1, B2, B3, and B4 (Zhao et al, 2017 ; Dai X. et al, 2020 ; Wang P. et al, 2020 ). Thus, the inhibitory activity of green tea extracts resulted from these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because CsWD40 promoted the regulation effects of CsMYB5e , resulting in higher PA biosynthesis than anthocyan in biosynthesis. In our previous studies, CsANR overexpression reduced anthocyanin production and promoted PA accumulation in the petals of tobacco plants [ 41 ]. In the Arabidopsis mutant of BAN (loss of function of ANR ), a high level of anthocyanin accumulated in the seed coat.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously demonstrated (Fischer et al 2014) that ANR silencing in strawberry leads to the early accumulation of anthocyanins in the fruit, by re-routing the flux from flavan-3-ols to anthocyanins. At the opposite, Zhao et al (2017) recently showed that overexpression of tea ( Camellia sinensis ) ANR genes in tobacco effectively leads to a significant loss of flower red-pigmentation by reducing their anthocyanin content. These results further support the hypothesis that the increased expression of a LG3a-located ‘CF1116’ ANR homoeoallele from the F. vesca –derived subgenome is responsible for the increased accumulation of pelargonidin-3-glucoside that likely underlies the M3a colour mQTL.…”
Section: Discussionmentioning
confidence: 99%